FAKTOR-FAKTOR YANG MEMPENGARUHI KECEMASAN PASIEN DALAM TINDAKAN KEMOTERAPI DI RUMAH SAKIT DR.MOEWARDI SURAKARTA - Umi Lutfa; Arina Maliya (Jurnal Berita Ilmu Keperawatan, 2008)
Background of The Study. Feeling worry at patient of cancer because them in fear of impact that happened, for example change of body image and death. Worry about the death can cause annoyed of medication process. Anticipated a patient age, education, frequency of chemotherapy and mount the adaptation have an effect on to patient dread in experiencing chemotherapy. Objective of Research. The target of this research are wish to know the influence patient age to storey; level of patient dread, mount the patient education to storey; level of patient dread, previous patient frequency about chemotherapy to storey; level of patient dread, and mount the patient adaptation to storey; level of patient dread. Research of Method. Research use the descriptive correlative design. Research conducted at Dr. Moewardi Hospital of Surakarta. The population of this research are 410 patient. Sample of the research are 44 patient. The technique of sampling is proportional sampling. Conclusions. Research result are: (1) the storey level dread of patient of chemotherapy at RSUD Dr. Moewardi are middle, that are counted 50% from totalizing responder, (2) there didn’t influence of patient age to dread storey level, ( 3) there didn’t influence of education of patient to storey level dread of patient, (4) there didn’t influence of frequency of patient about chemotherapy to storey ;level dread of patient of chemotherapy, and ( 5) there are influence of patient adaptation about chemotherapy to storey level dread of patient of chemotherapy at RSUD Dr. Moewardi Surakarta